Language endangerment: a multidimensional analysis of risk factors. Issue 1 (27th April 2020) - Bromham, L; Hua, X; Algy, C; Meakins, F
Abstract: The world is facing a crisis of language loss that rivals, or exceeds, the rate of loss of biodiversity. There is an increasing urgency to understand the drivers of language change in order to try and stem the catastrophic rate of language loss globally and to improve language vitality. Here we present a unique case study of language shift in an endangered Indigenous language, with a dataset of unprecedented scale. We employ a novel multidimensional analysis, which allows the strength of a quantitative approach without sacrificing the detail of individual speakers and specific language variables, to identify social, cultural, and demographic factors that influence language shift in this community. We develop the concept of the 'linguatype', a sample of an individual's language variants, analogous to the geneticists' concept of 'genotype' as a sample of an individual's genetic variants. We use multidimensional clustering to show that while family and household have significant effects on language patterns, peer group is the most significant factor for predicting language variation. Generalized linear models demonstrate that the strongest factor promoting individual use of the Indigenous language is living with members of the older generation who speak the heritage language fluently. Wright–Fisher analysis indicates that production of heritage language is lost at a significantly faster rate than perception, but there is no significant difference in rate of loss of verbs vs nouns, or lexicon vs grammar. Notably, we show that formal education has a negative relationship with Indigenous language retention in this community, with decreased use of the Indigenous language significantly associated with more years of monolingual schooling in English. These results suggest practical strategies for strengthening Indigenous language retention and demonstrate a new analytical approach to identifying risk factors for language loss in Indigenous communities that may be applicable to many languages globally.